A systematic review of knowledge sharing challenges and practices in global software development. Issue 6 (December 2016) - Zahedi, Mansooreh; Shahin, Mojtaba; Ali Babar, Muhammad
Highlights: We present systematic literature review of 61 primary studies (2000–September 2014) that empirically reported knowledge sharing challenges and practices in Global Software Development (GSD). We found knowledge sharing challenges and practices in GSD could be classified in 6 main themes: management, team structure, work processes/practices, team cognition, social attributes and technology. Regarding contextual settings, we found empirical studies were mainly conducted in offshore outsourcing collaboration model distributed between two sites. Most of the studied organizations were large enterprises. Abstract: Context: Global Software Development (GSD) presents significant challenges to share and understand knowledge required for developing software. Organizations are expected to implement appropriate practices to address knowledge-sharing challenges in GSD. With the growing literature on GSD and its widespread adoption, it is important to build a body of knowledge to support future research and effective knowledge sharing practices. Objective: We aimed at systematically identifying and synthesizing knowledge sharing challenges and practices. We also intended to classify the recurrent challenges and most frequently reported practices in different contextual settings. Method: We used Systematic Literature Review (SLR) for reviewing 61 primary studies that were selected after searching the GSD literature published over the last 14 years (2000–September 2014). We applied thematic analysis method for analysing the data extracted from the reviewed primary studies. Results: Our findings revealed that knowledge sharing challenges and practices in GSD could be classified in 6 main themes: management, team structure, work processes/practices, team cognition, social attributes and technology. In regard to contextual settings, we found empirical studies were mainly conducted in an offshore outsourcing collaboration model distributed between two sites. Most of the studied organizations were large enterprises. Many of the studies did not report any information for several contextual attributes that made it difficult to analyse the reported challenges and practices with respect to their respective contexts. Conclusion: We can conclude: (a) there is a higher tendency among researchers to report practices than challenges of knowledge sharing in GSD. (b) Given our analysis, most of the reported knowledge sharing challenges and practices fall under the theme of "work practices". (c) The technology related knowledge-sharing challenges are the least reported; we discussed the available technologies for supporting knowledge sharing needs in GSD. (d) The organizational contextual information is missing from a large number of studies; hence, it was not possible to investigate the potential relations between knowledge sharing challenges/practices and the contextual attributes of GSD teams. We assert the need of exploring knowledge sharing in the context of small/medium sized organizations to avoid the risk of findings being biased by specific empirical setting (e.g., large enterprises distributed between US and India).